2019
DOI: 10.1111/are.14454
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation by Coriandrum sativum seeds (Coriander) and its ameliorative effect on lead‐induced immunotoxicity in Nile tilapia ( Oreochromis niloticus L.)

Abstract: The current study was carried out to evaluate the effects of dietary supplementation of Coriandrum sativum seed powder (CP) and extract (CE) on some immune functions of Oreochromis niloticus, without or with exposure to the immunotoxicant metal lead (Pb). Fish (n = 300) were divided into ten groups, in triplicate. First group (Cont) was fed on the basal control diet. Second (CP20) and third (CP30) groups were fed on CP‐supplemented diets at 20 mg/kg and 30 mg/kg respectively, while fourth (CE20) and fifth (CE3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…The study showed activated lysozyme and phagocytic activities in European sea bass fed dietary coriander. Similarly, Ahmed et al (2020) andNaderi Farsani et al (2019) stated that Nile tilapia and rainbow trout fed dietary coriander had enhanced immune responses. Increased lysozyme and phagocytic activity indicate that European sea bass can tolerate the infection with pathogenic bacteria due to the role of lysozyme activity in breaking down the cell wall of pathogenic bacteria (Saurabh and Sahoo, 2008;Siwicki and Studnicka, 1987).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The study showed activated lysozyme and phagocytic activities in European sea bass fed dietary coriander. Similarly, Ahmed et al (2020) andNaderi Farsani et al (2019) stated that Nile tilapia and rainbow trout fed dietary coriander had enhanced immune responses. Increased lysozyme and phagocytic activity indicate that European sea bass can tolerate the infection with pathogenic bacteria due to the role of lysozyme activity in breaking down the cell wall of pathogenic bacteria (Saurabh and Sahoo, 2008;Siwicki and Studnicka, 1987).…”
Section: Discussionmentioning
confidence: 98%
“…Coriander powder is derived from the seeds of the coriander plant. The identification and composition of coriander powder were defined by following Ahmed et al (2020) and Naderi Farsani et al (2019). The formulated diets were dried at room temperature; then, after cooling, the diets were kept in plastic bags till used.…”
Section: Materials and Methods Diets And Experimental Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that our findings on the concoction in the rat experimental system on enhanced antibody production are consistent with some of the previous studies when only the C. sativum extracts were used. Different preparations of aqueous and ethanolic extract of C. sativum had shown immunostimulant activity in mice [ 19 ], chickens [ 20 ], and fish [ 21 , 22 ]. It is possible that the immunostimulatory activity observed in the concoction of C. sativum or C. fenestratum is attributable to the effect from C. sativum .…”
Section: Discussionmentioning
confidence: 99%
“…The seeds of C. sativum and stem of C. fenestratum have previously been shown to have anti-inflammatory activity when tested alone and as ethanolic concoctions of individual ingredients [ 17 , 18 ]. Some immunostimulatory activity has also been reported with aqueous and ethanolic concoctions of C. sativum when used as a single ingredient [ 19 22 ].…”
Section: Introductionmentioning
confidence: 99%